Dilated inferior vena cava: a common echocardiographic finding in highly trained elite athletes - Goldhammer, E.; Mesnick, N.; Abinader, E. G.; Sagiv, M. (Journal of the American Society of Echocardiography, 1999)
Typical structural features of the athlete's heart as defined by echocardiography have been extensively described; however, information concerning extracardiac structures such as the inferior vena cava (IVC) is scarce. Fifty-eight top-level athletes and 30 healthy members of a matched control group underwent a complete Doppler echocardiographic study. IVC diameter was determined in the subxiphoid approach 10 to 20 mm away from its junction to the right atrium. Measures reflect the median values between maximal inspiratory and expiratory values. IVC respiratory collapsibility index was determined as well. IVC in athletes was 2.31 +/- 0.46 cm compared with 1.14 +/- 0.13 cm in the control group (P <.001). Swimmers had an IVC diameter of 2.66 +/- 0.48 cm compared with 2.17 +/- 0.41 cm in other athletes (P <.05). The IVC was normal (<l.7 cm) in 5.2%, dilated (1.7 to 2.5 cm) in 70.7%, and very dilated (>/=2.6 cm) in 24.1% of athletes. The collapsibility index was 58% +/- 6.4% in athletes compared with 70.2% +/- 4.9% in the control group (P <. 001). Correlation was found between IVC size and VO(2) max (r = 0.81, P <.001) and the right ventricle (r = 0.81, P <.001) and with collapsibility index (r = -0.57, P <.05). Multiple regression analysis showed the impact of VO(2) max, cardiac index, and right ventricular and left ventricular end-diastolic dimensions on IVC diameter. IVC dilatation probably represents adaptation of an extracardiac structure to chronic strenuous exercise in top-level, elite athletes.